Ovarian Response, Pregnancy Outcomes, and Complications Between Salpingectomy and Proximal Tubal Occlusion in Hydrosalpinx Patients Before in vitro Fertilization: A Meta-Analysis - Ou, Hua; Ma, Xiao; Sun, Jie; Lin, Lin; Ling, Bin (Frontiers in Surgery, 2022)
Objectives: Contradictory findings exist in studies comparing salpingectomy and proximal tubal occlusion (PTO) in treating hydrosalpinx patients before in vitro fertilization (IVF). Therefore, this meta-analysis aimed to comprehensively compare ovarian response, pregnancy outcomes, and complications between salpingectomy and PTO in treating these patients. Methods: Embase, PubMed, and Web of Science were searched to identify relevant articles published from 1980 to August 31, 2020. Eight studies involving 716 hydrosalpinx patients before IVF were included, among whom 408 patients received salpingectomy, and 308 patients received PTO. The data were pooled; the standardized mean difference (SMD) or odds ratio (OR) was calculated. Results: PTO-treated patients had higher fertilization rate (SMD = 0.35, 95%confidence interval (95%CI): 0.11-0.59), while similar days of controlled ovarian hyperstimulation (COH) (SMD: 0.15, 95%CI: -0.36-0.67) and number of retrieved oocytes (SMD = -0.22, 95%CI: -0.54-0.10) compared with salpingectomy-treated patients. Furthermore, no difference of implantation rate (OR = 1.17, 95%CI: 0.62-2.20), clinical pregnancy rate (OR = 0.82, 95%CI: 0.59-1.15), ongoing pregnancy rate (OR = 0.64, 95%CI: 0.36-1.13) or live birth rate (OR = 0.67, 95%CI: 0.16-2.72) was shown between salpingectomy-treated patients and PTO-treated patients. Additionally, ectopic pregnancy rate (OR = 1.13, 95%CI: 0.21-5.92) and miscarriage rate (OR = 0.88, 95%CI: 0.31-2.48) were similar between salpingectomy-treated patients and PTO-treated patients. Conclusion: PTO exhibits a higher fertilization rate but no obvious benefits on days of COH, number of retrieved oocytes, pregnancy outcomes, and complications over salpingectomy in hydrosalpinx patients before IVF.